0482 Virtual Reality Guided Imagery for Insomnia (iVR): Preliminary Feasibility and Outcomes. (25th May 2022) - McCrae, Christina; McGovney, Kevin; Berry, Jasmine; Simenson, angelynn; Dillon, McCann
Abstract: Introduction: Chronic insomnia affects approximately 10% of adults and is associated with reduced quality of life, fatigue, impaired cognition, and increased risk for illness. Cognitive behavioral therapy for insomnia (CBT-I) is a recommended frontline treatment for chronic insomnia, but is not widely accessible as the number of trained CBT-I clinicians (<500) falls significantly short of the number of patients needing treatment. Digital delivery holds great potential for increasing access to CBT-I as well as other behavioral treatment approaches. Our team recently developed and conducted preliminary testing of a novel, brief virtual reality guided imagery for insomnia (iVR) in adults with chronic insomnia. Methods: 12 adults (Mage=38.2 years, SD=20.7, 50% female) with chronic insomnia completed 4-weeks of iVR delivered via Oculus Go headsets equipped with blue light blocking lenses and pre-loaded with a guided relaxation application, sleep hygiene instructions, and modified stimulus control instructions. Participants completed a Satisfaction Survey at post-treatment and the following outcome assessments at baseline, post-treatment, and 1-month follow-up: Insomnia Severity Index, State-Trait Anxiety Inventory, Fatigue Severity Scale, and 1-week of sleep diaries (sleep onset latency, wake time after sleep onset, total sleep time, sleep quality [1-poor, 5-excellent]). [KM1] Paired one-tailed t-tests were used to examine preliminary outcomes. Effect sizes (ES) are reported as Hedges G. Results: Adherence (#treatment weeks completed, M=3.5, SD=0.78) and Satisfaction (greater >8.8/10 on average for overall experience and likelihood of recommending to a friend) were high. Insomnia severity (7/28, ES=1.13, p<0.01), wake time after sleep onset (12 mins, ES=0.40, p=0.03), sleep onset latency (10 mins, ES = 0.36, p=0.04), and sleep quality (0.5/5, ES=1.08, p<0.01) improved following treatment. Gains were maintained at 1-month along with additional improvements in total sleep time (36 mins, ES=0.67, p=0.03) and trending improvement in fatigue (9/100, ES=0.46, p=0.05). State Trait Anxiety Inventory and Fatigue Severity Scale scores did not improve. Conclusion: Our pilot findings suggest iVR is feasible and promising treatment for chronic insomnia. Because the intervention can be pre-installed, iVR may be particularly useful for individuals with limited internet access (e.g., rural populations, military). Future research with a larger sample, randomized controlled design, and longer-term follow-up appears warranted. Support (If Any): Healium, Inc-PI McCrae